Characterization of breast cancer stem cells isolated from 4T1 cell line cultured in vitro - Phuong, Do Thi; Nga, Nguyen Thi; Cuc, Nguyen Thi; Thu Phuong, Vu Thi; Thao, Do Thi (Vietnam Journal of Biotechnology, 2018)
Breast cancer is the most common cancer in women of which the main causes of death are its relapse and drug resistance. Recently, researchers clarified a small population of cancer cells holding the abilities of self-renewal, unlimited propagation responsible for tumor progression, metastasis, therapy resistance, and tumor recurrence. These cells are termed as cancer sterm cells (CSCs), possessing characteristics of stem cells. Thus, cancer stem cells have become to be a potential target for cancerous drug discovery. They can be used in a new research model for establishing novel therapy as well as sreening new compounds that target CSCs. In our studies, we isolated cancer stem cells from 4T1 cell line using serum-free medium and non-adherent culture surface. Those CSCs clones were formed after 10 culturing days from 1 initial cell. The clones could initiate subtumorsphere better than 4T1 cells themselves. There were 3 selected clones named as Đ3G5, Đ3C3 and Đ4E7 which had mammosphere formation efficiency over 30% (31.67%, 36.33%, and 35.33%, respectively). These clones showed the significant withstanding against ellipticine and/or doxorobicin stronger than that of 4T1 cells (P<0.05). The IC50 values (inhibition of cell growth at 50%) of elliticine was 0.89 ± 0.07 μg/mL and of doxorobicin was 0.58 ± 0.04 μg/mL toward 4T1 cell growth while those values were 2 - 3 folds higher in our isolated cancer stem cell clones (P<0.05). Those clones also exhibited strong expression of several typical genes of stem cells such as nanog and Sox2.